Dynamic pull-in and pull-out analysis of viscoelastic nanoplates under electrostatic and Casimir forces via sinusoidal shear deformation theory. (April 2017) - Shokravi, M.
Abstract: In the present research, dynamic pull-in and pull-out analysis of viscoelastic nanoplate switch under electrostatic and intermolecular Casimir forces are studied. The Viscoelastic properties of the nanoplate are considered using Kelvin-Voigt model. Sinusoidal shear deformation theory is utilized for mathematical modeling of the structure due to its accuracy of polynomial function than other plate theories. The surface effects are considered based on Gurtin-Murdoch theory to enhance the accuracy of results. Considering size effects based on Eringen's nonlocal theory, motion equations are derived using Hamilton's principle and solved by Galerkin's method. Considering two boundary conditions of clamped in all edges (CCCC) and clamped in two edges and free in tow another edges (CCFF), the influences of various parameters such as small scale effect, surface layer, viscoelastic damping coefficient and applied voltage on the pull-in voltage, pull-in time, pull-in deflection and pull-out voltage are discussed in details. Numerical results indicate that considering small scale effects, the pull-in time and voltage as well as pull-out voltage are increased and decreased, respectively, for CCFF and CCCC boundary conditions. In addition, as the effective gap distance increases, the pull-out voltage tends toward the pull-out voltage. The results of this investigation can be used in control and optimum design of smart nano-electrical devices in advanced applications as smart controller. Graphical abstract: Highlights: Studying of viscoelastic silicon nanoplate as a nano-switch Using sinusoidal shear deformation theory with five unknown variables Considering electrostatic and intermolecular Casimir forces Analyzing pull-in voltage, pull-in time and pull-out voltage for the nano-switch Investigating the effect of surface layer and viscoelastic damping